Information systems, how many does our public administration need? (2017)
Information and communication technologies have taken on a global importance based on the globalization of markets, which in turn is based on the internationalization and publicity of information, which is now taken as a valuable resource for organizations, And therefore it is sought through the improvement of communication channels to make efficient use of information. The Colombian state is aware of the global dynamics and the importance and impact of the proper management of information in public administration has opted to modernize its state apparatus by renewing public management and therefore its information systems as a piece Key to this transformation. The SI information systems, being technological tools of management and information management become a key piece to measure the management and the impact of the public entities in the society, and therefore they become development objectives, objective that requires of Resources and commitment on the part of the entities. From now on we will see the importance of the information systems in the modernization of the Colombian state.